Dental health education with songs as an effort to increase knowledge of brushing teeth in elementary school students - Arif, Rayana Aulia; Barus, Adelina (Journal Center of Excellent : Health Assistive Technology, 2025)
Background: The 2018 Basic Health Research showed that only 2.8% of the Indonesian population had brushed their teeth at the correct time, namely in the morning after breakfast and at night before going to bed. Banten Province showed that the population aged ? 3 years in Banten Province had brushed their teeth at the correct time. One of the health promotion efforts is through education, where dental health education is closely related to a media. One of the educational media for elementary school children is children's songs. Objective: The purpose of this study was to analyze the effectiveness of increasing knowledge of brushing teeth before dental health education with songs in grade II students of SDN Rengas South Tangerang 2024. Method: The design of this study used a quasi-experimental design, with a research sample of 34 grade II A students of SDN Rengas using the total sampling method. The instrument used was a questionnaire sheet on how to brush teeth, then the method and media used were songs about Brushing Teeth. Data analysis used the Wilcoxon test. Results: Knowledge before and after being given education on Brushing Teeth with songs, in the good category, namely (67%) to (97%), in the sufficient category, namely (30%) to (3%), and in the less category, namely (3%) to none (0%). The average knowledge before education showed a figure of 77 with a good category. While the average knowledge after education was at 95, there was a difference in knowledge of 18 with p = 0.001. Conclusion: there was an increase in knowledge of brushing teeth with song education in elementary school children